Genome Editing of Isogenic Human Induced Pluripotent Stem Cells Recapitulates Long QT Phenotype for Drug Testing - Wang, Yongming (2014)
BACKGROUND: Human pluripotent stem cells (PSCs) play an important role in disease modeling and drug testing. However, the current methods are time consuming and lack an isogenic control. OBJECTIVES: To establish an efficient technology to generate human PSCs-based disease models with isogenic control. METHODS: The ion channel genes KCNQ1 and KCNH2 with dominant negative mutations causing long QT syndrome (LQTS) type-1 and -2, respectively, were stably integrated into a safe harbor AAVS1 locus using zinc finger nuclease (ZFN) technology. RESULTS: Patch-clamp recording revealed that the edited induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) displayed characteristic LQTS phenotype and significant prolongation of the action-potential duration (APD) compared with the un-edited control cells. Finally, addition of nifedipine (L-type calcium channel blocker) or pinacidil (KATP-channel opener) shortened the APD of iPSC-CMs, confirming the validity of isogenic iPSC lines for drug testing in the future. CONCLUSIONS: Our study demonstrates that PSC-based disease models can be rapidly generated by overexpression of dominant negative gene mutants.